AGEING IN PLACE FRAMEWORK AS REFERENCE GUIDE FOR HOUSING IN MALAYSIA: LANDED PROPERTY - Mohd Tobi, Siti Uzairiah; Fathi, Mohamad Syazli; Amaratunga, Dilanthi (PLANNING MALAYSIA, 2018)
The increasing ageing population due to improved quality of life from better healthcare services and lifestyle as well as development in technology calls for better support in the ageing process. Even though the aged population dramatically increases globally, surprisingly the construction sector and the housing system seem slow in adapting to the changing needs of the ageing population. Increasing evidence show that population ageing is a pervasive and unparalleled global phenomenon which presents many challenges towards social and economic growth. Therefore, this research focuses on the provision of better support services and facilities of landed property, as well as the creation of sustainable environment that is age-friendly and safe. Data were collected using semi-structured interviews, focus group discussion and document reviews. Findings from cross sectional content analysis and cognitive mapping could enhance the standard of living for senior citizens in Malaysia in the context of ageing in place. A foundation for developing a comprehensive guideline for elderly, particularly in the urban areas, is proposed to improve the health and welfare of senior citizens in Malaysia through the provision of better services, facilities and development in landed properties.